Physical activity in adolescents of different family socioeconomic status: the moderating role of gender - Zhang, Ting; Li, Ming; Zhang, Feng; Yang, Xiaofang; Sun, Pengwei; Yin, Xiaojian; Liu, Yuan; Guo, Yaru (Frontiers in Pediatrics, 2025)
BackgroundTo investigate the association between family socioeconomic status (SES) and the physical activity (PA) levels of adolescents, as well as the moderating effect of gender on this relationship.MethodsA total of 10,327 Chinese adolescents aged 12–17 were recruited to complete questionnaires regarding their SES and PA levels. “Physical Activity Questionnaire for Children and Adolescents Aged 7–18 Years” was utilized to examine the specific items, intensity, duration, and frequency of PA. The Kruskal–Wallis test and the Mann–Whitney U test were employed to compare PA time among adolescents across different groups. To analyze the interaction effect between gender and SES, the Scheirer-Ray-Hare test was conducted using R software. Additionally, SPSSAU was utilized to examine the moderating effect of gender and SES on PA.Result(1) Different intensities of PA: Overall, the times for LPA, MPA, VPA, MVPA, and TPA in the low SES group were 190 (100, 400) minutes, 190 (80, 400) minutes, 60 (0, 160) minutes, 290 (150, 570) minutes, and 580 (345, 925) minutes, respectively.The duration of PA at each intensity level in the low SES group was significantly lower compared to that in the middle and high SES groups (all P-values < 0.05). (2) Different PA types: The low SES group exhibited the shortest durations for both transportation PA (260 min) and exercise PA (155 min), while household PA was the longest (15 min)(all P-values < 0.05). (3) Moderating effect test: After controlling for relevant variables, the interaction term coefficient between gender and SES was statistically significant (B = −19.141, t = −2.059, P < 0.05).ConclusionAdolescents from low SES backgrounds exhibited the lowest levels of MVPA and TPA, which were mainly manifested in transportation PA and exercise PA. Gender moderates the relationship between SES and MVPA, with different SES levels having a more pronounced effect on PA in boys than in girls.